Perceived relative income and preferences for public good provision - Balietti, Anca; Budjan, Angelika J.; Eymess, Tillmann (AWI discussion paper series, 2023)
Guided by a theoretical framework, we study how perceived relative income affects preferences for public goods. In a randomized survey experiment, we inform respondents from India of their official income rank and elicit preferences for air quality, including actual contributions to environmental initiatives. Right-wing supporters withdraw contributions when perceived relative income increases. The effect coincides with diminished health concerns and lower intentions to utilize private protection measures against air pollution. In contrast, center-left supporters do not reduce contributions. A second survey experiment demonstrates the causality of the relationship using a novel treatment that exogenously shifts relative income perceptions.
Keywords: Graue Literatur